2023
DOI: 10.1021/acssuschemeng.3c00293
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Plastic with Bamboo: Eco-Friendly Disposable Tableware Based on the Separation of Bamboo Fibers and the Reconstruction of Their Network Structure

Abstract: Disposable bamboo fiber tableware is a novel type of product that utilizes sustainable, high-performance bamboo fiber to minimize plastic pollution. In this study, we developed a high-utility bamboo fiber tableware product by employing a novel hybrid fiber-membrane strategy: We used a combination of steam explosion technology and mechanical refining to achieve the “up-down” separation of bamboo. During the molding process, slender bamboo fibers mixed with starch were interwoven into a strong three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Although some electricity was used during the mechanical processing, no polluted water or air were generated. Finally, the only waste is bamboo dust, which can be recycled as a raw material for bamboo plastic composites, disposable bamboo fiber tableware, and bamboo-based carbon. To quantify the environmental impact of the bamboo film, we conducted a simple cradle-to-gate life cycle assessment (LCA) and compared it with that of cellulose (Figure D, Tables S2 and S3), which is another raw material used as an actuator. , Bamboo films showed lower environmental impacts on indicators such as global warming potential, terrestrial acidification, and fossil fuel resources used (Figure D). For example, the CO 2 footprint of the bamboo film is 0.1 kg CO 2 per kg, which is 93% less than that of cellulose and remarkable less than that of graphene …”
Section: Resultsmentioning
confidence: 99%
“…Although some electricity was used during the mechanical processing, no polluted water or air were generated. Finally, the only waste is bamboo dust, which can be recycled as a raw material for bamboo plastic composites, disposable bamboo fiber tableware, and bamboo-based carbon. To quantify the environmental impact of the bamboo film, we conducted a simple cradle-to-gate life cycle assessment (LCA) and compared it with that of cellulose (Figure D, Tables S2 and S3), which is another raw material used as an actuator. , Bamboo films showed lower environmental impacts on indicators such as global warming potential, terrestrial acidification, and fossil fuel resources used (Figure D). For example, the CO 2 footprint of the bamboo film is 0.1 kg CO 2 per kg, which is 93% less than that of cellulose and remarkable less than that of graphene …”
Section: Resultsmentioning
confidence: 99%
“…Bamboo can minimize greenhouse gas emissions in a number of ways. Bamboo grows fast and has a high capacity for carbon sequestration [48]. Bamboo products can store carbon for a long time and maintain a low or even zero carbon impact throughout the product life cycle.…”
Section: Advantages Of Bamboo Fibermentioning
confidence: 99%
“…A combination of steam explosion technology and mechanical refining is used to separate bamboo materials, and then the bamboo fibers are mixed with tapioca starch to prepare new bamboo fiber tableware. The prepared product has the characteristics of high strength, water resistance, oil resistance, temperature resistance, dissolution resistance, etc., and can be quickly and harmlessly degraded, which is an ideal substitute for traditional non-degradable plastics in food packaging applications [48].…”
Section: Application Of Bamboo Fiber Reinforced Polymer Composites In...mentioning
confidence: 99%
“…36 Natural fibrous membranes and the exploitation of their hydrophilic or hydrophobic nature in various applications are rising. Cavalcante et al demonstrated a new application of membrane contactors for developing superamphiphilic mycelium materials; 37 Chen et al reconstructed eco-friendly disposable tableware based on bamboo fiber separation and its network structure; 38 and Oldal et al used green solvents to prepare inherently sustainable CA nanofibers. 39 Herein, we propose, for the first time, a simple strategy to develop a functional textile based on trilayered porous membranes with unidirectional water transport performance and complete degradation for continuous moisture wicking (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%